Operations Resarch In Business Administration and Management - Maroto Álvarez, Concepción (Colección Académica, 2014)
Operations Research, Management Science or Business Analytics is a technology that helps improve business decision making. This book is focused on linear, integer, nonlinear and multiobjective programming, as well as multiple criteria decision making and metaheuristics (genetic algorithms). Excel Solver, LINGO, Expert Choice and D-Sight are the software used to solve decision making problems.